A percepção de acadêmicos de enfermagem sobre o processo de morte morrer no CTI - SANTOS, Christiane Tereza Aleixo dos (2020)
Death is a frequent phenomenon in the Intensive Care Centers, and when faced with the scenario the students end up suffering a very big impact, and their mental health ends up becoming fragile. The process of death and medical process is still in the process of death and death.Thus, the study presents the following questions: what are the perceptions of nursing students about the process of death and dying? And how these perceptions can influence your professional training. It aims to: Describe the perceptions of nursing students regarding the process of death and dying in the intensive care unit and analyze the implications of these perceptions for professional training. The data collection was done through a semistructured interview, guided by a script, elaborated based on the objectives of the study with open questions. The sample consisted of 30 nursing students from the eighth and ninth semester of nursing at the Federal University of Pará, in Belém do Pará. In order to analyze the data, we opted to work with the thematic analysis technique for the formation of the units. Thus, three guiding categories emerged for the study: Professional preparation for coping with the death and dying process; Death and its meanings; The applicability of professional posture in situations involving death and dying. In view of the above, it is noted that there is academic unpreparedness, that the difficulty of discussing the subject and the non-acceptance of death as part of life leave the professionals perplexed and distant from the patients in the imminence of dying, making decisions difficult and deal with the negative feelings generated.